Biological functionalization of poly (lactic-co-glycolic acid) with ammonia and chitosan–gelatin combined treatment for acupoint catgut-embedding therapy. Issue 15 (August 2021) - Fu, Shaoju; Zhang, Peihua
Polylactic-co-glycolic acid (PLGA) has attracted extensive attention in acupoint catgut embedding therapy (ACET). However, developing biological functionalization for ACET materials remains challenging to due to its poor surface properties. In this work, PLGA was first treated with ammonia solution, and chitosan–gelatin coating was then introduced onto the surface of PLGA braided thread to achieve biological functionalization. Characteristics such as structural, mechanical, and in vitro properties were then fully evaluated. The results showed that modified samples showed more surface roughness than non-modified ones, and weight and diameter changes in samples increased after coating treatment, together with surface hydrophilicity; mechanical properties such as tensile property and bending stiffness of samples were greatly enhanced. Non-coated samples exhibited no antibacterial properties, while that of coated samples showed different antibacterial properties against Escherichia coli and Staphylococcus aureus . No samples showed toxicity, with more than 75% cells viable. In sum, the strategy of surface-modified PLGA using a combined ammonia and chitosan–gelatin treatment showed great potential in the application of ACET.